Constructing Innocence: Representations of Sexual Violence in Upper Canada’s War of 1812 - Heaman, Elsbeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
This essay explores the way in which rape was represented in Upper Canada circa 1812. It draws upon a broadly defined Upper Canadian print culture that drew upon and reacted against wider trends, especially those prevalent in the United States. Whereas American newspapers spoke openly of sexual violence against American women during the War of 1812, Upper Canadian sources tended to suppress any such discussion, for reasons that reflect profound cultural and political differences. Americans stoked a rowdy, popular patriotism that Canadians distrusted and sought to avert. The analysis of national differences is contextualized within broader changes in the ways that rape was constructed in the press and the courts over the first half of the nineteenth century, in ways that worked to muffle women’s public voice. But the War of 1812’s most famous heroine, Laura Secord, was not silenced. Writing almost half a century later, Secord challenged discursive conventions of gender when she had her say and made herself a hero. The final section examines how Secord and her early commentators interwove literary signals of danger and respectability in their published accounts.